Role of Oyster Mushroom (Pleurotus ostreatus) Against Cecal Coccidiosis in Cobb 500 Broiler Chicken (Journal of Scientific Research, 2012)
A total of 25 day old Cobb 500 broiler chicks were purchased and randomly divided into five groups (A, B, C, D and E). Group A served as noninfected, non-supplemented control. Group B were infected and non-supplemented while chicks of group C, D and E were supplemented oyster mushroom (Pleurotus ostreatus) @ 50, 100 and 150 mg/kg body weight respectively with feed from 2-28 day of age. The chicks of group B, C, D and E were challenged orally with 1 x 104 sporulated oocysts of Eimeria tenella on 10th day. The anticoccidial efficacy of oyster mushroom was evaluated based on oocysts counts per gram (OPG) of feces, weight gain, morbidity and mortality, necropsy findings and histopathology. Concerning the mean OPG count, body weight gain (p